Geometrical structure of lead nuclei and of some other chemical elements - Aminov, Yu.A. (Вопросы атомной науки и техники, 2020)
The interior structure of nucleus of the chemical element lead is given in the form of shell sequence of polyhedrons. This sequence represented with the help of some arithmetic progression of positive numbers, which connects with hypothesis of α-particles synthesis of nuclei. Other chemical elements also are considering with this point of view. On the graph of abundance of chemical elements in Solar system picks correspond to these elements. In the work the Table of numbers of nucleons in nuclei of these elements is proposed and we obtain combinatoric type of polyhedrons, which considering as shells of these chemical elements. Внутрішня будова ядра хімічного елемента свинцю представлена у вигляді послідовності оболонок у формі многогранників. Ця послідовність пов’язана з певною арифметичною прогресією додатних чисел, котра має відношення до гіпотези α-часткового синтезу ядер. Інші хімічні елементи також розглянуті з цієї точки зору. На графіку поширення хімічних елементів у Сонячній системі цим елементам відповідають піки. У роботі запропонована таблиця чисел нуклонів в ядрах цих елементів, а також таблиця відповідних елементів. Отримано комбінаторний тип многогранних оболонок, які належать до складу ядер. Внутренняя структура ядра химического элемента свинца дана в виде последовательности оболочек многогранников. Эта последовательность строится с помощью некоторой арифметической прогрессии положительных чисел, которая связана с гипотезой α-частичного синтеза ядер. Другие химические элементы также рассмотрены с этой точки зрения. На графике распространенности химических элементов в Солнечной системе этим элементам соответствуют пики. В работе предложена таблица чисел нуклонов в ядрах этих элементов, а также соответствующая таблица элементов. Получен комбинаторный тип многогранных оболочек, входящих в состав ядер.